Özgön’den Konya’ya Uzanan Göç: Tacigül Özgen Küntüz’un Kimlik ve Anavatana Dair Aidiyet Duygusunu İfade Etme Biçimi - ESHNAZAROVA, Aikanysh; TOKTOGULOV, Beishenbek (SD Publisher, 2021)
First generation diasporic immigrants, who have diasporic experience due to the trauma of forced migration, have a strong sense of belonging to the homeland. Even, they can transfer this sense of belonging to the next generations without losing its liveliness. In addition, the sense of belonging to the homeland is an important factor affecting the identity formation of the next generations. This study aims to investigate the second-generation member of the diasporic immigrant Özgen family, the painter Tacigül Özgen Küntüz's sense of belonging to the region of origin, her identity formation process and the way she expresses them. The study will deal with the works created by the painter in terms of identity and belonging.